MODEL PEMBELAJARAN MUATAN LOKAL PKK DENGAN EXPERIENCE-BASED CAREER EDUCATION - KOKOM KOMARIYAH (Jurnal Kependidikan, 2004)
Abstract This research aims at developing an Experience-based Career Education model of instruction that has been tested empirically. This research is performed by using the approach of research and development, planned for two years. The first stage of this covers: identifying problem, testing the product feasibility, planning the model, validating and experimenting the model. This research involved several data resources, i.e. the household welfare education ‘local content’ teachers, the staff of the Yogyakarta Regional Office of Education DIY, school principals, education experts and practitioners and junior high school students. the data were collected by using questionnaire, interview and documentation and analyzed descriptively. The results indicate that the model is successful in improving the teachers’ ability in performing the instruction, improving the students’ motivation  in learning and overcoming the inadequacy of facilities and infrastructure in. Keywords: model of instructor, household welfare education ‘local content’, experience-based career education